PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PEREDARAN OBAT DAN MAKANAN TIDAK BERIZIN YANG DIPROMOSIKAN MELALUI MEDIA SOSIAL - Zai, Charisman Jaya; Rumapea, Parulian Ganda; Pakpahan, Kartina; Iansyah, Fauzi (Universitas Ekasakti, 2021)
The state has an obligation to protect, supervise every product that is circulated for consumption by the public. This study aims to identify and analyze the form of legal protection for consumers so that illegal drug and food circulation which is circulated through social media does not occur, analyze the criteria for drugs and food without a distribution permit, and forms of accountability for business actors who commit acts normative juridical research methodology using literature study. The data analysis of this research used a qualitative approach. Law Number 80 of 2017 concerning Drug and Food Control was established to protect the public against any drug product whose registration is not registered based on applicable regulations. Accountability for the distribution of illegal drugs can be subject to criminal sanctions based on Article 196 jo 197 of Law Number 30 of 2009 concerning health if it meets the elements of error and unlawful acts.